ANALISIS PROMOSI, STORE LAYOUT DAN SELF SERVICE YANG MEMPENGARUHI KONSUMEN DALAM MELAKUKAN IMPULSE BUYING (STUDI PADA KONSUMEN SUPERMARKET LOKA MALANG CITY POINT KOTA MALANG) - Pradini, Cesarika (Manajemen Bisnis, 2017)
The purpose of this research are 1 ) to find out whether the promotion, store layouts , and self service significantly influence toward impulse buying 2 ) to find out whether the promotion , store layouts , and self service influence simultaneously significant toward impulse buying. This research uses quantitative approach, the method whis is used in this research is accidental sampling; determine sample based on coincidence. It can be said that anyone who coincidentally meet the researcher and if the persons is suitable as data source, the researcher will ask the persons to fill out questionnaire which is later it will be use as sample. The population in this research was the consumers who shopped in Loka Malang City Point with the total of 100 respondents. The instrument for the analysis is research instrument tests which are validity and reliability test by using heteroscedasticity test, multicollinearity test, and linearity test. After that continued with multiple regression analysis. This research has a purpose to analyze the independent variable ( x ) in this case is the independent variable that affects to impulse buying , the variable among others is the variable sale , store layout , and self service . After all the research instrument testing, the last thing to do is hypothesis testing used t-test and f-test. Based on this research it can be concluded as follows: variable promotion , store layout , and self service significantly influence impulse buying in partial and simultaneous .